ATIM-33. NOA-16: A FIRST-IN-MAN MULTICENTER PHASE I CLINICAL TRIAL OF THE GERMAN NEUROONCOLOGY WORKING GROUP EVALUATING A MUTATION-SPECIFIC PEPTIDE VACCINE TARGETING IDH1R132H IN PATIENTS WITH NEWLY DIAGNOSED MALIGNANT ASTROCYTOMAS. (5th November 2018) - Platten, Michael; Schilling, Daniela; Bunse, Lukas; Wick, Antje; Bunse, Theresa; Riehl, Dennis; Green, Edward; Sanghvi, Khwab; Karapanagiotou-Schenkel, Irini; Harting, Inga; Sahm, Felix; Steinbach, Joachim; et al.
Abstract: In preclinical studies we have defined IDH1R132H as a clonal neoantigen presented on MHC class II. A peptide vaccine encompassing IDH1R132H induces tumor-specific T helper cell responses effective in controlling syngeneic IDH1R132H-mutant tumors in humanized mouse models. NOA-16 (NCT02454634) is a first-in-man, multicenter, phase I trial testing the safety and immunogenicity of an IDH1R132H peptide in incomplete Freunds adjuvant in patients with newly diagnosed, IDH1R132H mutant WHO °III and °IV astrocytomas. Between September 2015 and October 2016, 32 patients were enrolled in seven German sites. 23 patients (71.9%) received radiochemotherapy with temozolomide, six patients (18.8%) received radiotherapy alone and three patients (9.4%) received temozolomide alone. 249 vaccines were administered, 29 (90.6%) of the patients of the safety set (N=32) and 27 (90.0%) patients of the immunogenicity set (N=30) received all eight vaccines. No regime-limiting toxicity was observed. The majority of the patients (N=29, 90.6%) experienced treatment related adverse events (trAE), 1 (3.1%) of them had treatment related SAE. None of the reported AEs were severe. 28/30 (93.3%) patients, who were evaluable for immunogenicity, displayed mutation-specific T cellular (24/30 (80%)) or humoral (26/30 patients (87%)) immune responses not detectable before vaccination. Until end of study no deaths were observed. 4/32 (12.5 %) patients had PD according to RANO criteria, all other patients (N=28, 87.5%) had SD. 12/32 (37.5%) patients displayed pseudoprogressions after the initiation of the vaccine. Single-cell T cell receptor (TCR) sequencing allowed for the identification of IDH1R132H-specific TCRs. In conclusion, NOA-16 met its primary endpoints by demonstrating safety and immunogenicity of a mutation-specific IDH1R132H peptide vaccine given with standard of care in patients with newly diagnosed IDH1R132H mutant malignant astrocytoma.